Altruism or self-interest in tomorrow's veterinarians? A metric conjoint experiment and cluster analysis - Feakes, Adele; Lindsay, Noel; Palmer, Edward; Steffens, Paul (Frontiers in Veterinary Science, 2023)
This study explores the competing traits of other-orientation (an individual's caring concern for the well-being of others) and self-interest in entrants to the veterinary profession. The Theory of Other-Orientation holds that other-orientation can impact an individual’s decision-making heuristics in both helping and non-helping contexts. In patient-focused contexts, highly other-oriented (veterinary) professionals may care too much for others and suffer immediate or cumulative financial and personal costs of such caring. At the same time, other-orientation can enhance job-related attitudes and outcomes, such as job satisfaction. Anticipating a range in other-orientation and self-interest, we purposefully surveyed Australian final-year veterinary, science, nursing, entrepreneurship, and engineering students. We used a metric conjoint experiment to reveal other-orientation and self-interest. Respondents rated eight job scenarios with orthogonally arranged high and low levels of three job characteristics (n = 586). In a two-way MANOVA, respondents of different disciplines (but not genders) differed in other-orientation or self-interest. Veterinary (and engineering) respondents were less other-oriented than nursing respondents. Veterinary (and entrepreneurship) respondents were more self-interested than nursing respondents. Using K-Means cluster analysis, we confirmed four distinct profile groupings – altruistic/self-sacrificing, 'both other-self', self-interested and selfish – aligning with the discourse in the literature and represented differently between disciplines and veterinary schools. Respondents of one of three veterinary schools stood out for the most members (19%) in the altruistic/self-sacrificing group. Our finding of the 'both other-self' group adds to the literature, which considers that though separate constructs, it is hard for other-orientation and self-interest to co-exist. This mix of traits may be helpful for sustainability and well-being, especially for professionals involved in high-frequency and intensity, patient-focused interactions, such as veterinarians. However, the proportion of the 'both other-self' profile was greater for nursing (50%) than veterinary (28%) respondents, highlighting an area for more research on why. The metric conjoint experiment may interest researchers as an adjunct or alternative to 'self-report' Likert-scaled items. Our study discusses implications and needs for further research on the impact of other-orientation and self-interest on veterinary school admissions processes, the hidden or taught curricula, job-related attitudes and beliefs, and well-being and professional sustainability in the veterinary sector.